2003
DOI: 10.1002/chin.200340015
|View full text |Cite
|
Sign up to set email alerts
|

Raney Ni‐Sn Catalyst for H2 Production from Biomass‐Derived Hydrocarbons.

Abstract: For Abstract see ChemInform Abstract in Full Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
133
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(135 citation statements)
references
References 11 publications
0
133
0
2
Order By: Relevance
“…Native Ni oxide may form, but probably it is too thin to be detected. After 1 h, the Al met and AlO x peaks disappeared and were replaced by a peak at higher binding energies corresponding to those of Al 2 O 3 and/or Al(OH) 3 . The corresponding O 1s spectra (figure 4b) can be well fitted by two components at binding energies of 532.7 and 533.9 eV, which correspond to the binding energies of Al 2 O 3 and Al(OH) 3 , respectively [22].…”
Section: Process Of Activationmentioning
confidence: 93%
See 3 more Smart Citations
“…Native Ni oxide may form, but probably it is too thin to be detected. After 1 h, the Al met and AlO x peaks disappeared and were replaced by a peak at higher binding energies corresponding to those of Al 2 O 3 and/or Al(OH) 3 . The corresponding O 1s spectra (figure 4b) can be well fitted by two components at binding energies of 532.7 and 533.9 eV, which correspond to the binding energies of Al 2 O 3 and Al(OH) 3 , respectively [22].…”
Section: Process Of Activationmentioning
confidence: 93%
“…We have overcome this problem by directional solidification [11,12] and have succeeded in cold-rolling this compound into thin foils 23 lm in thickness [13]. Recently, we also found that intermetallic compound Ni 3 Al powder showed high catalytic activity and selectivity for methanol decomposition (CH 3 OH fi 2H 2 + CO) after alkali-leaching treatment [14,15]. These results suggest a possibility of the Ni 3 Al foils to be used both as catalysts and as structural sheets in the microreactors.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Commercially, hydrogen has been produced from catalytic steam reforming of fossil fuels, for example, methane [1]. To reduce greenhouse gas emissions, hydrogen should be derived from renewable energy sources such as bioethanol [2][3][4]. As a consequence, ethanol steam reforming has been studied, as it provides an alternative fuel source for hydrogen production [4][5][6].…”
Section: Introductionmentioning
confidence: 99%